Improved location and positioning in WiMAX networks with virtual MIMO base stations - Awang Md Isa, Azmi; Mohd Zin, Mohd Shahril Izuan; Mohamad Isa, Mohd Sa'ari; Md Saat, Mohd Shakir; Haron, Nor Zaidi; Zakaria, Zahriladha (American Scientific Publishers, 2014)
Conventional Location and Positioning (L&P) methods rely on the availability of base station (BS) locations as well as the mitigation of propagation effects. It is known that location estimation accuracy suffers in poor geometric dilution of precision (GDOP) caused by BS location as conventional location algorithms generate large GDOP values which correspond to poor geometrical topology. In addition, NLOS effects cause large errors in time of arrival (TOA) readings, thus affecting MS estimation accuracy. In this paper we introduce a novel concept of virtual BS (VirBS) utilizing multiple input multiple output (MIMO) technology and enable applying it to improve L&P accuracy. The results of the simulations demonstrate that the proposed algorithm allows up to 30 percent improvement in L&P accuracy without additional expenditure on network architecture.